Freezing-thawing effect and slake durability of some rocks from cold regions of Nepal and Japan - Dhakal, Ganesh P; Kodama, Junichi; Goto, Tatsuhiko (Journal of Nepal Geological Society, 2007)
Freeze-thaw and slake durability (wet-dry) tests were conducted on the welded tuff, carbonates (limestone from Japan and dolomite from Nepal), sandstone (from Japan), and schist (from Japan and Nepal) samples collected from the northern parts of Japan and the Higher Himalaya of Nepal. The freeze-thaw experiments conducted on limestone and sandstone from Japan and dolomite and schist from Nepal show that the rock samples are resistant to deterioration and breaking. No cracks are seen even after 300 cycles of freeze-thaw test in both large and small cubic samples of these rocks. However, in the welded tuff and schist from Japan, cracks initiate earlier but extend slower in the schist than in the welded tuff. Slake durability tests of all the samples were performed in pure water. However, the welded tuff was also tested in 0.1M and 1M NaCl solutions and in seawater. Similarly, porosity, tensile strength, and water absorption of all the samples were also measured. A tendency to decrease in slake durability with an increase in porosity is observed. The results reveal that the slake durability of the schist from Nepal is higher than that of the schist from Japan. However, regarding carbonate rocks, the slake durability of the limestone from Japan is higher than that of the dolomite from Nepal. Journal of Nepal Geological Society, 2006, Vol. 33 p.45-54